Porcine epidemic diarrhea: a review of current epidemiology and available vaccines - Song, Daesub (Clin Exp Vaccine Res, 2015)
Porcine epidemic diarrhea virus (PEDV), an Alphacoronavirus in the family Coronaviridae, causes acute diarrhea, vomiting, dehydration, and high mortality rates in neonatal piglets. PEDV can also cause diarrhea, agalactia, and abnormal reproductive cycles in pregnant sows. Although PEDV was first identified in Europe, it has resulted in significant economic losses in many Asian swine-raising countries, including Korea, China, Japan, Vietnam, and the Philippines. However, from April 2013 to the present, major outbreaks of PEDV have been reported in the United States, Canada, and Mexico. Moreover, intercontinental transmission of PEDV has increased mortality rates in seronegative neonatal piglets, resulting in 10% loss of the US pig population. The emergence and re-emergence of PEDV indicates that the virus is able to evade current vaccine strategies. Continuous emergence of multiple mutant strains from several regions has aggravated porcine epidemic diarrhea endemic conditions and highlighted the need for new vaccines based on the current circulating PEDV. Epidemic PEDV strains tend to be more pathogenic and cause increased death in pigs, thereby causing substantial financial losses for swine producers. In this review, we described the epidemiology of PEDV in several countries and present molecular characterization of current strains. We also discuss PEDV vaccines and related issues.